16. PRACTICE OF STANDARD PRECAUTIONS AMONG NURSES AT HOA BINH PROVINCIAL GENERAL HOSPITAL IN 2021 (Vietnam Journal of Community Medicine, 2022)
Objective: Evaluation of standard preventive practices of nurses at Hoa Binh general hospital in 2021Subject and method: The cross-sectional descriptive study was conducted with 284 nurses workingat Hoa Binh General Hospital from 03/2021 to 12/2021Results: Nurses practicing hand hygiene account for a high proportion of work content. Still, 30,6%of nurses occasionally use face shields/goggles when there is a risk of splashing/splashing blood/fluids of a sick person and 28,9% wear gowns when at risk of infection. The proportion of hospitalnurses who achieved the practice of some standard preventive content accounted for 59,6%.Conclusion: The proportion of nurses practicing standard prevention by job accounts for a lowproportion of work contents.
Keywords: Standard prevention, hospital, nosocomial infections.